Multinational retrospective analysis of bridging therapy prior to chimeric antigen receptor t cells for relapsed/refractory acute lymphoblastic leukemia in children and young adults - Maike Breidenbach; Peter Bader; Andishe Attarbaschi; Claudia Rossig; Roland Meisel; Markus Metzler; Marion Subklewe; Fabian Mueller; Paul-Gerhardt Schlegel; Irene Teichert von Lüttichau; Jean-Pierre Bourquin; Gabriele Escherich; et al. (Journal of Hematology & Oncology)
Abstract Anti-CD19 chimeric antigen receptor T cells (CAR) are a well-established treatment option for children and young adults suffering from relapsed/refractory B-lineage acute lymphoblastic leukemia. Bridging therapy is used to control disease prior to start of lymphodepletion before CAR infusion and thereby improve efficacy of CAR therapy. However, the effect of different bridging strategies on outcome, side effects and response to CAR therapy is still poorly understood. In this retrospective, multinational study, real-world data were collected from 14 different sites in Germany, Austria and Switzerland on 88 patients receiving 93 2nd-generation CAR therapies. Bridging therapy was classified into the categories 1) no systemic therapy (15/93 treatments), 2) low-intensity therapy (38/93 treatments) and 3) high-intensity therapy (39/93 treatments). We analyzed the impact of bridging regimens on clinical outcome. Patients receiving a high-intensity bridging therapy had a significantly higher tumor burden at time of eligibility compared to patients treated with a low-intensity or no systemic bridging therapy. They suffered significantly more from bacterial adverse events and mucositis. Overall survival was significantly better for patients who did not receive any bridging therapy in comparison to patients who had been treated with a low- or high-intensity bridging regimen. In conclusion, in this retrospective cohort, high-intensity bridging therapy has not improved the outcome in terms of overall and progression-free survival in comparison to a low-intensity therapy. Yet, high-intensity bridging therapy was associated with more adverse events. Our study suggests that a low-intensity bridging regimen may be preferred whenever tumor burden and disease kinetics allow this treatment strategy.